Global connectedness and local innovation in industrial clusters - Turkina, Ekaterina; Van Assche, Ari (Journal of International Business Studies, 2018)
In today’s knowledge economy, clusters are a key driver of a country’s competitiveness. Yet a cluster’s technological base is now more than ever influenced by constituent firms’ actions to tap into distant knowledge sources. Drawing on a social network perspective, and distinguishing between horizontal versus vertical organization-based linkages, we explore the effects of a cluster’s connectedness to foreign locations on its innovation performance. We show that improvements in horizontal and vertical connectedness both stimulate a cluster’s innovation performance, but that their relative effects vary across cluster types. Innovation in knowledge-intensive clusters disproportionately benefits from enhancements in their constituent firms’ horizontal connectedness to foreign knowledge hotspots. Innovation in labor-intensive clusters mostly gains from stronger vertical connections by their firms to central value chain players abroad. We discuss the implications of our findings for research on global knowledge sourcing and cluster upgrading.